Floppy's phonics book 12 - Hunt, Roderick
Level 2 Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 3 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.